Peningkatakan Kemampuan Anak Mengenal Konsep Bilangan Melalui Permainan Kartu Angka di Kelompok B TK Aisyiyah Pulau Payung Kecamatan Rumbio Jaya - Astuti Astuti (LPPM Universitas Pahlawan Tuanku Tambusai, 2016)
This study by low background backs children's ability to recognize the concept of numbers. The purpose of this study was to determine the increase in the ability of the child to know the concept of numbers through the method of card numbers in group B at TK Aisyiyah Payung Island Rumbio Jaya subdistrict. As the subjects in this study were children and teachers in group B in the academic year 2013/2014 the number of children of 20 people. While the object is the child's ability to know the concept of numbers through the game card numbers. The stages are passed in classroom action research, namely: 1) Planning / Preparation action, 2) Implementation Actions, 3) observation, and. 4) Reflection. The data source of this research are group B, teachers and documents. Collecting data using observation, testing and documentation. Data analysis using descriptive techniques percentage. The results showed that the method scorecards can improve the ability to know the concept of group B TK Aisyiyah number Umbrella Island districts Rumbio Jaya Kampar